The Influence of Product Quality on Purchasing Decisions Mediated by Brand Trust for Injection Products At CV Surya Fajar Multitama - Khodijah; Sari Siahaan, Febri; Rasyiddin, Ahmad (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of product quality on purchase decisions with brand trust as a mediating variable for injection products at CV Surya Fajar Multitama. The background of this research is based on the importance of product quality as one of the main factors in building trust in a brand, which in turn can encourage consumers to make purchases. In an era of increasingly intense business competition, companies are required to maintain consistent quality to create a brand image that is reliable and trustworthy. This research employs a quantitative approach with data analysis conducted using the Structural Equation Modeling (SEM) method based on SmartPLS. The sample consisted of 97 respondents, who were consumers of CV Surya Fajar Multitama, selected through purposive sampling. The data collection instrument was a questionnaire consisting of items measuring product quality, brand trust, and purchase decision variables. The results of the study show that product quality has a positive and significant effect on brand trust, with a coefficient value of 0.718 and a p-value of 0.000, indicating that the better the product quality perceived by consumers, the higher their trust in the brand. In addition, product quality was also found to have a direct influence on purchase decisions, with a coefficient of 0.460 and a p-value of 0.000, suggesting that consumers’ perception of product quality plays an important role in driving their purchasing decisions. Furthermore, brand trust was found to have a significant effect on purchase decisions, with a coefficient of 0.385 and a p-value of 0.000, indicating that consumers’ trust in a brand strengthens their confidence in making purchases. The indirect effect of product quality on purchase decisions through brand trust was also significant, with a coefficient value of 0.276 and a p-value of 0.000, showing that brand trust acts as a partial mediator in this relationship. These findings highlight the importance of continuously maintaining product quality to build brand trust and strengthen consumers’ purchasing decisions.